Toni Morrison’s Tar Baby: Deconstructing the African Myths and Subversion of White Values - Devi, N Rama (Mindscape: A Journal of English & Cultural Studies, 2024)
Myths, legends, and folk tales form an inseparable and indispensable ingredient of the repertoire of any culture or community with an identity of its own and hence extremely important for an oppressed race or community of people to reclaim their identity, retrieve the lost glories of their ravaged culture and relate and connect them once again to the world. The African American women in general and Toni Morrison in particular despite being triply prejudiced against class, race and sexism strived very hard to preserve their culture and act as the pioneers in enriching, updating its relevance to the succeeding generations of their people in different times and corners of the world even as they condemn some of the deterrents the younger people tend to fall for from time to time. One of the chief concerns of Tar Baby is to make the reader see the way in which the ‘meaning’ eludes, slips through without allowing the reader to pin down as a result of which it becomes plural and contested rather than singular and uncontested. This research paper also makes use of Derrida’s concept of ‘difference,’ to foreground that the exact meaning of words and myths being is always elusive due to different reasons. Meaning is seen arising from the interplay of a number of signifiers and also from what a signifier is not as to what it is. Tar Baby examines the relationships between power structures on the one hand and myths and folk tales on the other, the power structures being gender, class, race, nationality, and geographical setting. The world that is rife with these arrangements is constructed rather differently as against the expectations of the readers - with the personification of natural forces.